Thermal performance enhancement of eutectic PCM laden with functionalised graphene nanoplatelets for an efficient solar absorption cooling storage system - Singh, R. P. (2021)
The present work investigates the thermal enhancement of a binary eutectic phase change material (PCM) (150–200 °C), laden with different concentrations of COOH-functionalized Graphene nanoplatelets (f-GNP) for a multi-effect solar cooling thermal storage system. The novel nano-composite is prepared by varying the weight concentration of f-GNP from 1% to 5% in a pristine eutectic salt of LiNO3-KCl (50:50) using the standard nano synthesis protocol. The microstructure, dispersion uniformity are evaluated using scanning electron microscope (SEM) and thermophysical properties of the nano-composite are characterized using dynamic Differential scanning calorimetry (DSC). The thermal conductivity enhancement due to the doping of f-GNP is studied through a series of experimental trials conducted with Laser flash analysis (LFA). The obtained data is plotted and compared with a more robust theoretical thermal conductivity model. It is found that thermal conductivity rises by 104% with f-GNP dispersions, which reflects the improved thermal performance of the storage system. The specific heats of the solid and liquid phase show an increase of 80% & 38% respectively at f-GNP concentration of 5%. Finally, the effect of doping f-GNP on the conjugate heat transfer inside the PCM and fluid flow of HTF is investigated in a vertical shell and tube type storage system, suitable for the double effect solar cooling system. The f-GNP dispersions accelerate the heat storage process with a maximum decrease of 17.3% in the total melt duration. In addition, the role of increased viscosity on the natural convection is simultaneously studied with the increased thermal conduction due to nanoplatelets dispersions.